Global Repositioning of Nations Analyzing the Competitive Advantage of India and the UAE - Ahmed, Faisal; Khan, Shalzzia (Gyan Management Journal, 2007)
Competitiveness is inevitably becoming an instrument for nations to measure their socio-economic prowess and subsequently to position and reposition their brand equity in a globalizing society. This paper duly investigates the actionable concept of competitive advantage for the fast developing landscapes of the globe. India and United Arab Emirates (UAE) are the two nations, which the paper considers to examine. The analysis is being undertaken considering various bases including the organizational frameworks within them, the existing business environment and the regional geopolitical stability prevalent thereof. Both the economies are now becoming a lucrative hub for global investors; and the paper therefore, evaluates their contemporary competitive advantage across socio-economic pursuits and the new strategies they are/ could be using to make a global repositioning of their brand. It must be noted that a nation's prosperity depends on its ability to compete strategically by enhancing its productivity to become still closer to selfsufficiency. A close observation and comparative analysis of both the countries, with reference to emerging industries. services sector, infrastructure development and other promising variables, are being duly made.
Keywords: Global Repositioning; Nations Analyzing; Competitive Advantage; instrument